10–25 GHz frequency reconfigurable MEMS 5-bit phase shifter using push–pull actuator based toggle mechanism. (15th May 2015) - Dey, Sukomal; Koul, Shiban K
Abstract: This paper presents a frequency tunable 5-bit true-time-delay digital phase shifter using radio frequency microelectromechanical system (RF MEMS) technology. The phase shifter is based on the distributed MEMS transmission line (DMTL) concept utilizing a MEMS varactor. The main source of frequency tuning in this work is a bridge actuation mechanism followed by capacitance variation. Two stages of actuation mechanisms (push and pull) are used to achieve a 2:1 tuning ratio. Accurate control of the actuation voltage between the pull to push stages contributes differential phase shift over the band of interest. The functional behavior of the push–pull actuation over the phase shifter application is theoretically established, experimentally investigated and validated with simulation. The phase shifter is fabricated monolithically using a gold based surface micromachining process on an alumina substrate. The individual primary phase-bits (11.25°/22.5°/45°/90°/180°) that are the fundamental building blocks of the complete 5-bit phase shifter are designed, fabricated and experimentally characterized from 10–25 GHz for specific applications. Finally, the complete 5-bit phase shifter demonstrates an average phase error of 4.32°, 2.8°, 1° and 1.58°, an average insertion loss of 3.76, 4.1, 4.2 and 4.84 dB and an average return loss of 11.7, 12, 14 and 11.8 dB at 10, 12, 17.2 and 25 GHz, respectively. To the best of the authors' knowledge, this is the first reported band tunable stand alone 5-bit phase shifter in the literature which can work over the large spectrum for different applications. The total area of the 5-bit phase shifter is 15.6 mm 2 . Furthermore, the cold-switched reliability of the unit cell and the complete 5-bit MEMS phase shifter are extensively investigated and presented.